Sedimentology and sequence stratigraphy of the Early Cretaceous Centenario Formation (upper member) in the north-eastern border of the Neuquén Basin, Argentina. (June 2021) - Pazos, Pablo J.; Novara, María E.; Iñigo, Juan; Comerio, Marcos
Abstract: The Centenario Formation is a unit known in literature by the content of oil reservoirs in the Productive Trend Río Colorado (PTRC) situated in the north-eastern border of the Neuquén Basin. The formation is composed of a lower and upper member, the latter being the object of this study. The analysis of five wells distributed in a cross section of 10 km length, allowed the analysis of 150 m of cored succession that cover almost all the stratigraphic extent of the upper member. Facies analysis allowed defining ten of them (A–J), recording storm, tidal, and fluvial processes, as well as trace-fossils mainly of the Cruziana and Cruziana - Skolithos ichnofacies and microbialites distributed in different parts of the succession. Nine Facies Associations (I–IX) were defined and them account for marine, marginal-marine and fluvial environments. The marine record documents deposits from the offshore to shoreface that form part of a first and thickest stratigraphic sequence (Sequence I) dominated by a starved transgression (TST), followed by a shallow and wave-dominated delta system (HST) evidencing multiple directions of progradation, and showing quartz dominated composition derived from old sedimentary units. An erosive sequence boundary denotes the beginning of a new depositional cycle (Sequence II). It starts with estuarine facies (TST) containing the coarsest deposits in the entire succession (conglomerates) that are probably correlatable with incised valleys and fluvial deposits documented in outcrops and subsurface. A remarkable change to a lithic composition with abundant volcaniclastic fragments evidences a supply from younger units than the underlying sequence; additionally, tidal action is amplified by a non-lineal coast. A marine interval records the end of the transgression (MFZ), and later a coarsening upward arrangement (HST) product of bay head deltas grading laterally into mud flats. The uppermost part of the unit records the change in the coast line with the advance of fluvial deposits denoting the new sedimentary change with the reorganization of the depositional system (Sequence III). It starts with unconfined fluvial deposits (LST) that present the peculiarity of bimodal grain-size deposits and well-sorting as a result of reworking of previous eolian deposits. The abundant kaolinite contrasts with the underlying sequence and indicates meteoric water input. The fluvial deposits, oil reservoirs, are sealed by marginal marine deposits on top (TST). The succession is incomplete by erosion of the intra-Senonian unconformity, but the stacked sequences exhibit a similar staking trend as in the outcropping Agua de la Mula Member of the Agrio Formation. The last one is a good surface analog unit for comparing sedimentary processes, sequence stratigraphy and ichnology. Taking into account previous studies and outcrops and subsurface correlations, this study restricts the upper member of the Centenario Formation time-equivalent to the Agua de la Mula Member of the Agrio Formation; a post-earliest Barremian age is disregarded. The integration of all available information confirms that conglomerates recorded in subsurface, and also outcrops are the result of incised valleys related to sea level drops. In this sense the Chachauén volcano outcrops are probably the exposed records of the Centenario Formation, rather than the Agrio Formation. Finally, this study confirms a complex sedimentary evolution of the north-eastern basin border, with tectonic controls and a variable coastal line that allows explaining short distance facies changes. This study demonstrates the usefulness of ichnological approaches with sedimentology, particularly in intervals completely oil-impregnated where sedimentary features are frequently difficult to analyze for paleoenvironmental interpretations. Highlights: The upper Centenario Formation contains several stratigraphic sequences. Marine, marginal-marine and fluvial deposits are documented. Coastal morphology explains progradation patter but also tidal amplification. The Chachachauén volcano is the only known outcropping analog of the studied succession. Tectonic activity controlled the sequence architecture.